1994
DOI: 10.1007/bf02462048
|View full text |Cite
|
Sign up to set email alerts
|

Structure of water-in-oil microemulsions of AOT by infrared spectroscopy

Abstract: (ricevuto il 28 Ottobre 1994)Summary. --The structure of water in water/AOT/n-heptane reverse micelles has been studied as a function of the [H20]/[AOT] ratio (W) by using the absorption IR due to O--H stretching modes in the 3800-3000 cm-1 range. The results show that the IR spectra can be expressed as a sum of contributions from bound-and bulk-like water. The fraction of water in the two ~,regions-within the water pool was evaluated as a function of W. The ,(bound), water region seems to hold 3.5 water molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…TSPP H‐ and J‐type aggregation in RM : These results suggest the existence of different aggregates of TSPP in AOT reverse micelles which depend on the amount of solubilized water and local pH. As mentioned before18c, 22c, 33 the water in these RM has peculiar solvent properties which are quite different from those of free water (higher viscosity, lower dielectric constant) and therefore the water activity must be such that the usual concept of pH is no longer valid. Moreover, the size of the water‐pools (or even the shape for some RM)18c, 34 depends on ω 0 .…”
Section: Discussionmentioning
confidence: 79%
“…TSPP H‐ and J‐type aggregation in RM : These results suggest the existence of different aggregates of TSPP in AOT reverse micelles which depend on the amount of solubilized water and local pH. As mentioned before18c, 22c, 33 the water in these RM has peculiar solvent properties which are quite different from those of free water (higher viscosity, lower dielectric constant) and therefore the water activity must be such that the usual concept of pH is no longer valid. Moreover, the size of the water‐pools (or even the shape for some RM)18c, 34 depends on ω 0 .…”
Section: Discussionmentioning
confidence: 79%
“…FTIR results (50) revealed that only the first few water molecules bind to the and Na ϩ ions. So, additional wa-Ϫ SO 3 ter molecules would, then, localize in the core forming water pools.…”
Section: Piroxicam In Reversed Micelles Of Aotmentioning
confidence: 99%
“…These systems, nanometer-sized water droplets stabilized in heptane by the surfactant sodium bis(2-ethylhexyl) sulfosuccinate (AOT), have been characterized extensively with respect to their size, shape, size dispersion [19,20], and the nature of the water pool at the core of the micelle [21,22]. For these measurements, AOT inverse micelles were prepared according to standard methods, using a surfactant purified as in Ref.…”
mentioning
confidence: 99%
“…This could be because of changes in the nature of the water pool as its size decreases. In the smallest micelles, a substantial fraction of the internal water is bound rather than free water [22]. The calculated surface tension relies on parameters, such as the interior liquid density and its static dielectric constant, which could be affected by the increasingly strained hydrogen bond network.…”
mentioning
confidence: 99%